The interaction in the group of self-help: support in the rehabilitation of mastectomized women - Pacífica Pinheiro Cavalcanti; Ana Fátima Carvalho Fernandes; Maria Socorro Pereira Rodrigues (Rev Rene)
Descriptive and exploratory study that it aimed at to create favorable conditions of interaction among the women, stimulating reflections on life events, with prominences to the repercussions psychosocial of the mastectomy; to promote the elevation of the self-esteem and of the life quality seeking the personal harmonization; to unchain existences groups that provide change of experiences and “relieves”. Ten integral women of the group GEPAN (Group from Teaching, Research, Self-help and Attendance to the Mastectomized woman) were interviewed in the months of December of 2000 to February of 2001. The depositions were organized in agreement with the content analysis and contained in the categories: share of feelings and needs, mechanisms of solution of problems; I space educational; I space interactive creating friendships and change of experiences. It could be noticed that the communication is a fort mechanism used by the mastectomized women, to reinforce and to elevate the self-esteem, to improve the life quality and to obtain an interior harmonization.